2015
DOI: 10.2147/jpr.s90434
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic and psychological factors with persistent pain after cosmetic thoracic surgery

Abstract: The genetic control of pain has been repeatedly demonstrated in human association studies. In the present study, we assessed the relative contribution of 16 single nucleotide polymorphisms in pain-related genes, such as cathechol-O-methyl transferase gene (COMT), fatty acid amino hydrolase gene (FAAH), transient receptor potential cation channel, subfamily V, member 1 gene (TRPV1), and δ-opioid receptor gene (OPRD1), for postsurgical pain chronification. Ninety preoperatively pain-free male patients were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…COMT gene has four important SNPs: rs4680, rs6269, rs4633 and rs4818, all of which produce three pain sensitivity haplotypes: HPS, APS, and LPS. The present study failed to obtain an exclusive conclusion, but the correlation between the haplotype and opioid consumption cannot be ignored [12,25,[32][33][34]45]. Furthermore, some recent studies have begun to explore the relationship between genegene (COMT and OPRM1) interactions to the pain susceptibility and opioid analgesic effect.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…COMT gene has four important SNPs: rs4680, rs6269, rs4633 and rs4818, all of which produce three pain sensitivity haplotypes: HPS, APS, and LPS. The present study failed to obtain an exclusive conclusion, but the correlation between the haplotype and opioid consumption cannot be ignored [12,25,[32][33][34]45]. Furthermore, some recent studies have begun to explore the relationship between genegene (COMT and OPRM1) interactions to the pain susceptibility and opioid analgesic effect.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, the results form Orrey and Kolesnikov suggested that patients without LPS haplotype had maximum pain and would require a higher opioid amount [21,32]. Meanwhile, APS haplotype might associate with the lowest pain perception but involve long-term postsurgical pain [33,34]. Besides the haplotype of COMT, the interaction between OPRM1, sex, and COMT may also affect patients' pain perception [12,35].…”
Section: Systematic Review Of Comt and Postoperative Painmentioning
confidence: 99%
“…Pain catastrophizing has turned out as relevant predictor in several studies (Edwards et al, 2009;Theunissen et al, 2012;Masselin-Dubois et al, 2013;Schreiber et al, 2013;Burns et al, 2015) and is also increasingly acknowledged as psychological risk factor in comprehensive reviews (Niraj and Rowbotham, 2011;Chapman and Vierck, 2017). However, pain anxiety and pain hypervigilance have to date rarely been tested (Lautenbacher et al, 2010;Dimova et al, 2015). In addition, depression and anxiety are still highlighted as the main psychological factors implicated in the transition from acute to chronic post-operative pain (Hinrichs-Rocker et al, 2009;Chapman and Vierck, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated pain intensity and pain-related disability were assessed in the first post-operative session (T1; acute pain, predictor) and again in the second post-operative session (T2; chronic pain, outcome). This study was part of a larger prospective study also including additional predictors such as experimental pain testing and cortisol levels which are not reported here (Lautenbacher et al, 2009(Lautenbacher et al, , 2010Dimova et al, 2015). The PCS (Sullivan et al, 1995) was developed as a measure of catastrophizing related to pain.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation